Automatic induction of translation lexicons from aligned parallel corpus - Caseli, Helena de M.; Nunes, Maria das Graças V. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2007)
Translation lexicons are one of the most important linguistic resources for machine translation. However, this bilingual set of word and multiword correspondences requires a lot of manual work to be built. This paper describes a method to automatically build translation lexicons by extracting knowledge from PoS-tagged and lexically aligned parallel corpora. Preliminary experiments were carried out on Brazilian Portuguese, Spanish and English parallel texts. The results showed that 85% of pt–es and 89% of pt–en entries are plausible correspondences. These results were obtained taking into consideration only the classes of entries which achieved the best results.